2018
DOI: 10.1152/ajpendo.00048.2018
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of theIgf2gene alters hepatic lipid homeostasis and gene expression in the newborn mouse

Abstract: Newborns with intrauterine growth-restriction are at increased risk of mortality and life-long co-morbidities. Insulin-like growth factor-II (IGF2) deficiency in humans as well as in mice leads to intrauterine growth restriction and decreased neonatal glycogen stores. The present study aims to further characterize the metabolic and transcriptional consequences of Igf2 deficiency in the newborn. We found that, despite being born significantly smaller than their wild-type (Igf2) littermates, brain size was prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Although further studies are needed to validate the finding in an independent Chinese sample, our study together with the Dutch famine studies indicates that the IGF2 gene is important in lipid metabolism in human. The finding is supported by a recent study among mice, which demonstrated that Igf2 knockout mice displayed altered expression levels of genes involved in lipid and fatty acid metabolisms [25]. Early-life nutrition supply, development and growth, and lipids in adulthood warrant further investigation.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Although further studies are needed to validate the finding in an independent Chinese sample, our study together with the Dutch famine studies indicates that the IGF2 gene is important in lipid metabolism in human. The finding is supported by a recent study among mice, which demonstrated that Igf2 knockout mice displayed altered expression levels of genes involved in lipid and fatty acid metabolisms [25]. Early-life nutrition supply, development and growth, and lipids in adulthood warrant further investigation.…”
Section: Discussionmentioning
confidence: 61%
“…The IGF2 gene encodes insulin-like growth factor II and plays a key role in human development and growth. Animal studies revealed that lgf2 knockout mice mimicked nutritional deficiency in utero and resulted in growth restriction and neonatal glycogen stores reduction [25]. The gene is maternally imprinted and paternally expressed [2628], and methylation changes in the gene persist until at least middle age [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, insulin-like growth factor 2 expression in prostate cancer is regulated by promoter-specific methylation (Kuffer et al 2018). Disruption of this gene alters hepatic lipid homeostasis and gene expression in the newborn mouse (Lopez et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Oil Red O staining was performed as described previously, with minor modifications. 22 Cryosections were incubated with 0.5% (w/v) Oil Red O in propylene glycol (Electron Microscopy Sciences, Hadfield, PA) at 60°C for 10 minutes. Staining was quantified by imaging 10 random fields/section (200× magnification), and then measuring Oil Red O-positive areas using a macro written in Image J.…”
Section: Liver Tissue Stainingmentioning
confidence: 99%